2011
DOI: 10.1016/j.aap.2011.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Speed maintenance under cognitive load – Implications for theories of driver behaviour

Abstract: No model of driver behaviour has yet managed to achieve widespread acceptance and use in the field of traffic psychology, par tly due to the difficulty in testing many of the theories. However, one class of theories, the motivational theories, can be usefully split into two groups, and the differences between them can then be examined. One group posits the constant monitoring and targeting of a cer tain subjective variable, often risk, as the controlling factor in driving. The other group however states that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 22 publications
4
21
0
Order By: Relevance
“…This more cautious driving behavior could be a way of compensating for or adapting to the greater effect on the HL group when driving complexity increased. The driver behavior adaptation (or compensation) observed, decreased driving speed, and disregard of the Secondary task conforms well with previous research (Fuller, 2005;Lewis-Evans, 2011). The finding that the phonological similarity effect only affects the HL group more in critical situations also points at the effect of driving complexity.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…This more cautious driving behavior could be a way of compensating for or adapting to the greater effect on the HL group when driving complexity increased. The driver behavior adaptation (or compensation) observed, decreased driving speed, and disregard of the Secondary task conforms well with previous research (Fuller, 2005;Lewis-Evans, 2011). The finding that the phonological similarity effect only affects the HL group more in critical situations also points at the effect of driving complexity.…”
Section: Discussionsupporting
confidence: 77%
“…Manipulation of driving speed along with degree of engagement in Secondary tasks is claimed to be the primary mechanisms for this maintenance (Fuller, 2005). Simulator studies have demonstrated that distraction tasks (both visual and cognitive) lead to decreased speed and a difficulty in maintaining a certain speed (Engström, 2005;Lewis-Evans, 2011). Tsimhoni (2003) found, in a driving simulator study with a Secondary task and varying complexity of the road condition, that the total time allocated to the Secondary task increased significantly with a more complex driving task (sharp curves vs. straight road vs. parking).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same general pattern of results, where CL selectively impairs non-automatized aspects of driving, has also been demonstrated for other aspects of driving performance such as lane keeping [28], speed selection [29,30] and gap acceptance at intersections [31] (again see [2] for a detailed review).…”
Section: Introductionmentioning
confidence: 63%
“…At this point there is no consensus about the exact psychological processes underlying driving behavior. Depending on the theoretical framework, the level of (subjective) risk, workload, or a general feeling of comfort is either maintained or avoided (e.g., risk homeostasis theory, the zero-risk theory, risk allostasis theory, safety margin model (Näätänen and Summala, 1976; Wilde, 1982; Fuller, 2005; Summala, 2005; see also: Lewis-Evans et al, 2011). To make it even more complex, drivers alter the level of workload in practice through behavioral adaptations.…”
Section: Introductionmentioning
confidence: 99%